Selective removal of problem individuals as an environmentally responsible approach for managing shark bites on humans. (15th August 2020) - Clua, Eric E.G.; Linnell, John D.C.; Planes, Serge; Meyer, Carl G.
Abstract: Selective removal of problem individuals following shark bite incidents would be consistent with current management practices for terrestrial predators, and would be more effective and more environmentally responsible than current mass-culling programs. In parallel, and in addition to traditional forensics analysis, we recommend the routine collection of shark DNA from wounds or devices following shark bite incidents in order to genetically identify the individual responsible. This approach would require creating an extensive database of shark identities in high-risk areas against which to compare DNA forensically recovered from shark bite incidents. At a local and regional scale, we propose utilizing existing shark tagging programs and artificial shark aggregation sites to collect DNA, behavioural and morphological data for the database, and to facilitate removal of problem individuals. In several places around the world, selective removal of problem individuals would not be significantly more expensive and definitely less environmentally-destructive than traditional approaches and would also help reconcile people and sharks by underlining individuality in shark behaviour. Highlights: Indirect proofs suggest that fatal bites on humans are linked to problem individuals rather than environmental factors or shark densities. Instead of unselective mass fishing campaigns, we recommend the selective removal of sharks that have already perpetrated an attack. Problem individuals would be identified through a two-fold genetic approach. On one side, an individual DNA profile (fingerprinting) of the shark would be obtained from the victims' wounds or bitten devices. On another side, extensive databases would allow to gather individual DNA profiles, visual cues or tag identities to identify and remove the sharks.